1913
DOI: 10.1021/ie50049a009
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Exposure on Bitumens.

Abstract: I 5 3 Obtained from distillation of bitumens: This includes petroleum pitch, either "straight" or "cut back." 4 Obtained from the "oxidation" of bitumens: This includes "blown" petroleum pitches. 5 Obtained from the "sulfurization" of bitumens: This includes the so-called "Dubb's asphalt," obtained by heating petroleum residues with sulfur. 6 Variable Origin: I t may be of animal, vegetable or mineral origin and includes both natural and artificial products. 7 Hydrocarbon Complex: Often contains oxygen, nitrog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1962
1962
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The oxidative aging of asphalt binder has been studied for almost a century. Hubbard and Reeve examined the effects of outdoor weathering on the physical and chemical properties of paving-grade asphalt cements, finding that oxidation, and not volatilization alone, is responsible for the changes in asphalt binder properties over time (1). Subsequent studies have confirmed the Hubbard and Reeve finding (2,3).…”
Section: Low-temperature Oxidation Kinetics Of Asphalt Bindersmentioning
confidence: 92%
“…The oxidative aging of asphalt binder has been studied for almost a century. Hubbard and Reeve examined the effects of outdoor weathering on the physical and chemical properties of paving-grade asphalt cements, finding that oxidation, and not volatilization alone, is responsible for the changes in asphalt binder properties over time (1). Subsequent studies have confirmed the Hubbard and Reeve finding (2,3).…”
Section: Low-temperature Oxidation Kinetics Of Asphalt Bindersmentioning
confidence: 92%
“…During storage at room temperature for 12 h, no phase separation was observed. After standing for a period of storage, the appearance of the samples had changed slightly depending on the amount of 16AG in the mixture (Figure S1): StA alone showed a distinctive gloss, indicating a smooth surface; StA–16AG(1) showed an appearance similar to that of StA, although it was slightly matte; and StA–16AG(5) and StA–16AG(10) both showed a completely matte appearance. Atomic force microscopy revealed that the StA surface was covered with bee-like structures and terrace pattern assemblies (Figures and S2), which was consistent with a previous report. In contrast, the surfaces of the materials containing 16AG were characterized by stripes or fiber-like structures with a width ca.…”
Section: Resultsmentioning
confidence: 99%
“…Aging in asphalt pavements has been recognized and studied for almost a century. Hubbard and Reeve ( 1 ) published the results of an initial study that examined the effects of a year of outdoor weathering on the physical (weight, hardness, etc.) and chemical (solubility) properties of paving-grade asphalt cements.…”
mentioning
confidence: 99%